7x=-3(5x-8)

Simple and best practice solution for 7x=-3(5x-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x=-3(5x-8) equation:



7x=-3(5x-8)
We move all terms to the left:
7x-(-3(5x-8))=0
We calculate terms in parentheses: -(-3(5x-8)), so:
-3(5x-8)
We multiply parentheses
-15x+24
Back to the equation:
-(-15x+24)
We get rid of parentheses
7x+15x-24=0
We add all the numbers together, and all the variables
22x-24=0
We move all terms containing x to the left, all other terms to the right
22x=24
x=24/22
x=1+1/11

See similar equations:

| 3n+8=-21 | | 2x+4x+x=252 | | 5r^2-3r=6 | | 11t+5=84-6t | | -x/7+2=13 | | (2^x)^2-3.2^x+2=0 | | 6/1x=-3/11 | | 13=−11−(6m−11)+6m | | 100+2x=729 | | 8c+4c+c=65 | | (4x+2)+(7x-11)=90 | | 18x(3x+5=10) | | -5x+(x+6)=123,75 | | 4x2x=992 | | 21+9y=12y | | x-(2x3)=2 | | –18q+10q+16q–3=–19 | | 65=v2/5+19 | | 4/x=10-6 | | 6–p=9 | | p–6=9 | | 10^(x-3)=100000 | | 2(4.5x+4.5)=-2(2.5x-8) | | p=9–6 | | -12-6m=-(3m-3) | | 2x+20/2=18; | | 27-3a=12 | | 8.25h=429 | | 9a-3a=46 | | 12+x=-3(x-2)+3x | | 13^-x-6=6^9x | | 4x-5=14x15 |

Equations solver categories